THE RECOVERY OF GOLD FROM A PREAGNANT GOLD-THIOSULFATE LEACH SOLUTION USING ION EXCHANGE RESIN - SURATMAN SURATMAN (Puslitbang tekMIRA, 2008)
The loading of gold and copper from a pregnant gold thiosulfate leach solution onto ion exchange resin and the subsequent elution of these metals have been investigated. In this study, strong basic resins of Amberjet-4200 and IRA-400 were used and thiocyanate was used as eluent. It was found that on Amberjet-400, the gold loading reached about 2-3 kg/t, in correspondence to 0.4 ppm gold in the effluent.On IRA-400, the performance was almost exactly the same loading as on Amberjet- 4200 but with the effluent gold concentration being slightly higher. In leach solutions, copper is present in much higher concentrations than gold, since it is added as a catalyst for gold dissolution. The maximum Cu loading obtained on Amberjet-400 was about 22 kg/t while it was about 24 kg/t on IRA-400. These results indicate that gold can be removed from thiosulfate solutions rapidly and loaded on resins to very high concentrations. Subsequent gold elution with thiocyanate ions was very efficient; the concentration of gold on resin was reduced from about 2-3 kg/L down to less than 10 ppm (99,9% elution) under ambient temperature in 2-4 hours.